Effect of the Cross-Linking Modification on Corn Stalk Fiber Reinforced Polypropylene Composites. (February 2019) - Liu, Shanshan; Li, Ke; Zou, Yu; Chen, Juan
Abstract: In this study, corn stalk fiber (CSF) was used as a reinforcer to prepare wood plastic composite (WPC). The primitive CSF was subjected to alkali treatment in a low alkali solution to expose the cellulose fiber. Alkali-treated CSF (AT-CSF) was cross-linking modified with chitosan and glutaraldehyde. Then, the untreated CSF (UT-CSF) and the cross-linked modified CSF (CL-CSF) were added to polypropylene (PP) with different contents (10 wt%, 20 wt%, 30 wt%, 40 wt%), respectively. The morphology, mechanical, thermal and water absorption behaviours of WPC were investigated in detail. The results indicated that the crosslinking modification is an efficient method to improve the mechanical properties of WPC. Compared with UT-CSF, the crystallinity index (CrI) of CL-CSF was increased from 33.8% to 39.5%. The cross-linking modification promoted an increase in flexural strength of 19.2% and an increase in flexural modulus of 8.3% compared to the composite reinforced by UT-CSF. The water absorption of the composite reinforced by CL-CSF was lower than the composite reinforced by UT-CSF.